2010
DOI: 10.1007/s00466-010-0481-5
|View full text |Cite
|
Sign up to set email alerts
|

High-speed impact of electromagnetically sensitive fabric and induced projectile spin

Abstract: This work deals with the dynamic contact of a rigid body with a deformable electromagnetically sensitive fabric structure, represented by a network model. Of particular interest are the electromagnetically induced forces generated on the fabric, which are proportional to the external electric field (E E X T ) and the velocity crossed with the external magnetic field (v × B E X T ). These forces transmit reactions to the rigid contacting object, which can induce rotational motion. Modeling and simulation of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 49 publications
(87 reference statements)
0
16
0
Order By: Relevance
“…For details on a wide variety of relaxed models, we refer the reader to works dating back to Pipkin [28], Buchholdt et al [8], Pangiotopoulos [27], Bufler and Nguyen-Tuong [9] and Cannarozzi [10,11], Steigmann [33], Haseganu and Steigmann [14][15][16] and Atai and Steigmann [1,2]. Relaxed formulations have served as a foundation for computational models describing rupture of ballistic fabric shielding in Zohdi [36,43,46], Zohdi and Steigmann [37], Zohdi and Powell [41] and Powell and Zohdi [29] and are the basis for the present approach.…”
Section: Yarn-segment Network Representation Of Fabricmentioning
confidence: 99%
See 4 more Smart Citations
“…For details on a wide variety of relaxed models, we refer the reader to works dating back to Pipkin [28], Buchholdt et al [8], Pangiotopoulos [27], Bufler and Nguyen-Tuong [9] and Cannarozzi [10,11], Steigmann [33], Haseganu and Steigmann [14][15][16] and Atai and Steigmann [1,2]. Relaxed formulations have served as a foundation for computational models describing rupture of ballistic fabric shielding in Zohdi [36,43,46], Zohdi and Steigmann [37], Zohdi and Powell [41] and Powell and Zohdi [29] and are the basis for the present approach.…”
Section: Yarn-segment Network Representation Of Fabricmentioning
confidence: 99%
“…The expression in (39) can also be used for time step enlargement, to reduce computational effort, if convergence is met in less than K d iterations. Numerous parameter studies of this algorithm can be found in Zohdi [38][39][40][41][42][43][44][45][46].…”
Section: To This End One Writes (S(δtmentioning
confidence: 99%
See 3 more Smart Citations